Implementasi Balanced Scorecard sebagai Pengukuran Kinerja Rumah Sakit Ibnu Sina Pekanbaru - Wahyuni, Putri; Martias, Dony (Jurnal Rumpun Ilmu Ekonomi, 2024)
This research is a quantitative study that aims to determine how the implementation of Ibn Sina Hospital performance measurement with the balance scorecard approach. This study uses primary and secondary data obtained through the company's financial statements and questionnaires filled out by employees and patients. Performance from a customer perspective measured by customer satisfaction indicators measured in the current year shows the level of customer satisfaction in the "Very Satisfied" category with a score of 63%. The performance of the Financial perspective of the four indicators has "Fairly Good" results because the results of the NPM Ratio have increased results, namely by 0.10%, ROI has decreased results, namely by 0.04%, the performance of the Effectiveness Ratio has decreased by 8.72%, and the Efficiency ratio has decreased by 8.85%. The overall performance of the Internal Business perspective can be said to have "poor" results because BOR has an average value of 40.73%, ALOS Ratio with an average of 2 days, BTO Ratio with an average of 52 times, TOI Ratio with an average of 7 days, NDR Ratio shows an average of 12.85%, and GDR shows a decrease of 2.70%. The performance of the learning and growth perspective as a whole can be said to have "good" results with a score of 84%.